ON $(ALPHA ,BETA)$-FUZZY IDEALS OF TERNARY SEMIGROUPS - Davvaz, Bijan (Journal of the Indonesian Mathematical Society, 2013)
In this paper, we introduce the concept of generalizedfuzzy ideals in ternary semigroups, which is a generalization of the fuzzyideals of semigroups. In this regard, we define ($α ,β $)-fuzzyleft (right, lateral) ideals, ($α ,β $)-fuzzy quasi-ideals and ($α ,β $)-fuzzy bi-ideals and invetigate some related properties ofternary semigroups. Special concentration is paid to ($\in ,\in \vee q$)-fuzzy left (right, lateral) ideals, ($\in ,\in \vee q$)-fuzzy quasi-idealsand ($\in ,\in \vee q$)-fuzzy bi-ideals. Finally, wecharacterize regular ternary semigroups in terms of these notions.DOI :Â http://dx.doi.org/10.22342/jims.19.2.120.123-138